Cover Picture: Exposing Differences in Monomer Exchange Rates of Multicomponent Supramolecular Polymers in Water (ChemBioChem 3/2016). Issue 3 (3rd February 2016) - Baker, Matthew B.; Gosens, Ronald P. J.; Albertazzi, Lorenzo; Matsumoto, Nicholas M.; Palmans, Anja R. A.; Meijer, E. W.
Abstract : The cover picture shows an artist′s rendition of a peptide‐functionalized supramolecular monomer leaving one supramolecular polymer and inserting itself quickly into another. Although multicomponent and dynamic systems hold great promise for use in future generations of molecular therapeutics and biomaterials, it is often difficult to ascertain the position and behavior of the individual components of such a complex system. Utilizing water‐soluble benzene‐1, 3, 5‐tricarboxamide (BTA) polymers, we have directly shown the ability of peptide‐functionalized BTA monomers to readily incorporate into BTA‐based polymers, while retaining basic polymer characteristics. Several experimental techniques show high similarity between the peptide functionalized and unfunctionalized polymers, but we were able to catch the initially swift exchange of peptide‐functionalized monomers in a mixed system. These results show the importance of detailed spatiotemporal knowledge of individual components within multicomponent systems, leading to confidence in the design of such systems and, potentially, direct observation of their interactions with biological targets. More information can be found in the communication by E. W. Meijer et al. onpage 207 in Issue 3, 2016 (DOI:10.1002/cbic.201500606 ).